2009
DOI: 10.1152/ajpheart.00525.2008
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular regional wall curvedness and wall stress in patients with ischemic dilated cardiomyopathy

Abstract: Geometric remodeling of the left ventricle (LV) after myocardial infarction is associated with changes in myocardial wall stress. The objective of this study was to determine the regional curvatures and wall stress based on three-dimensional (3-D) reconstructions of the LV using MRI. Ten patients with ischemic dilated cardiomyopathy (IDCM) and 10 normal subjects underwent MRI scan. The IDCM patients also underwent delayed gadolinium-enhancement imaging to delineate the extent of myocardial infarct. Regional cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
4
74
0
1
Order By: Relevance
“…The application of the method on three real subjects showed its capability to capture more complex motion and strain patterns. In the healthy subject, physiologically meaningful strain curves were found: consistently with previous findings [23,24] almost uniform circumferential shortening and increasing thickening were assessed from LV base to apex. Moreover, LV torsion was consistent with data from tagged MRI and Doppler tissue imaging [25], both in terms of time-course and maximal values.…”
Section: Analysis Of Left Ventricle Strains and Torsionsupporting
confidence: 87%
“…The application of the method on three real subjects showed its capability to capture more complex motion and strain patterns. In the healthy subject, physiologically meaningful strain curves were found: consistently with previous findings [23,24] almost uniform circumferential shortening and increasing thickening were assessed from LV base to apex. Moreover, LV torsion was consistent with data from tagged MRI and Doppler tissue imaging [25], both in terms of time-course and maximal values.…”
Section: Analysis Of Left Ventricle Strains and Torsionsupporting
confidence: 87%
“…The magnitude of LV curvedness and WT values in the current study are comparable to those published elsewhere for patients with ischemic cardiomyopathy. 7,11 In addition, it is clear from Fig. 5 that, as one proceeds from the base to apical portions of the LV, the curvedness increases, and WT decreases, as expected.…”
Section: Discussionsupporting
confidence: 72%
“…Also, only end-diastolic images are used in this study. Our framework can be extended to utilize the end systolic phase, where the effects of LV remodeling are more pronounced, 7,29 and to analyze change in shape metrics over the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…If significant PR is found, cardiac MRI is performed to quantify PR severity and RV function (20). Many studies have shown that MRI is the best and most comprehensive approach to quantify the three dimensional (3-D) ventricular geometry and function (4,25,(47)(48), compared with echocardiography (16,41), ventriculography (14,46), angiography (33), and indicator-dilution methods (10). In patients with demonstrable severe PR and borderline RV function, serial MRI assessment becomes mandatory for timing of pulmonary valve replacement (PVR; Ref.…”
mentioning
confidence: 99%